Service Learning in Medical Education: Basic Approaches to Discipline Design - M. V. Prokhorova; O. R. Chepyuk; A. E. Mazanova; N. G. Briandinskaia; S. V. Nemirova (Высшее образование в России)
The paper proposes an approach to the design of the Service Learning discipline in a medical university, based on a detailed sociological study, a comparative review of the experiences of other countries, and the results of a pilot project at the Privolzhsky Research Medical University (Nizhny Novgorod). The aim of this study is to develop recommendations for the organisational support and content of Service Learning (subject types, target groups, formats), taking into account the medical students’ identified motivation to undertake projects with a volunteering component. The results showed that medical students have a particular motivation to participate in the discipline that is different from that of students of other disciplines (in the study, the control sample consisted of students in the social sciences and humanities): they emphasise the development of professional skills and the improvement of medical knowledge. Medical students choose projects related to direct clinical practice and public health, emphasising their interest in the practical application of knowledge and social responsibility. The main task of the discipline – the formation of civicism, social responsibility, moral values – is organically achieved in the medical students training. On the other hand, the tight schedule and rigid academic discipline in medical university require stability and certainty in the educational process, which is at odds with the project activity logic, that is characterised by flexibility and changeability of the external environment. The search for optimal organisational conditions for the implementation of project activities in a medical university can be the subject of further research on the topic of the publication.